Problems of Interinstitutional Interaction in Phthisiatrics - Khudaiberdieva Madina Jabborovna (Genius Journals, 2024)
A survey of 584 tuberculosis patients, 92 TB doctors and 144 general somatic network therapists showed that every second patient with tuberculosis (55.1%) experiences a negative attitude of others towards their personality. The need to create a public organization similar to the “Association of Relatives and Friends of People with Tuberculosis” was supported by 70.1% of TB patients, 63.1% of TB doctors and 52.2% of therapists. Analysis of the data obtained indicates that the need to create a department for chronic tuberculosis patients in the TB service is ripe, which confirms the opinion of 94.5% of TB doctors. The obtained comparative analysis data confirmed the lack of regular assistance from charitable organizations in anti-tuberculosis institutions
Keywords: tuberculosis; method; survey